The Intrinsic Inferiority of Efficiency Wages to Damages and Conditional Bonuses - Gerrit G.A. de Geest; Guiseppe Dari Mattiacci; J.J. Siegers (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2004)
In this paper, we argue that, as an enforcement mechanism, efficiency wages are intrinsically inferior to damages and to conditional bonuses – an alternative positive sanction system overlooked in the labor economics literature, under which rents are only paid if monitoring has effectively taken place (and the employee is not found shirking). While all three alternatives succeed in incentivizing agents and satisfy the participation constraint of non-shirking employees, damages (and negative sanctions in general) do so at lower costs because they do not require the payment of any rents. Of the two positive sanction systems, conditional bonuses are less expensive than efficiency wages because the latter also pay rents when no monitoring has taken place and may allow employees who are found shirking to keep some rents. Moreover, we find that monitoring levels are inefficiently low under efficiency wages. While efficiency wages (if they are completely non-retroactive) remove the employer's incentive to falsely sanction the employee, they solve this appropriation problem in a less rational way than some decoupling mechanisms that can be used under damages and conditional bonus regimes. Therefore, it seems extremely unlikely that employers would ever opt for efficiency wages on such a massive scale that structural unemployment would result, as Shapiro and Stiglitz (1984) suggested.
Keywords: 330; contract remedies; carrots; corruption; structural unemployment; decoupling